The hepatic transcriptome is differentially regulated by a standardized meal in healthy individuals compared to patients with fatty liver disease - Josephine Grandt; Christian D. Johansen; Anne-Sofie H. Jensen; Mikkel P. Werge; Elias B. Rashu; Andreas Møller; Anders E. Junker; Lise Hobolth; Christian Mortensen; Mogens Vyberg; Reza Rafiolsadat Serizawa; Søren Møller; et al. (PLoS ONE, 2025)
The human liver is dynamic organ with minute to hourly adaptions in response to feeding. Patients with non-alcoholic fatty liver disease (NAFLD) and cirrhosis have altered transcriptomic features compared to controls but how and if food intake affects such is unknown in humans. Our aim was to investigate the hepatic transcriptome at both fasting and postprandial states in patients with NAFLD, cirrhosis, and healthy controls and secondly to develop a browsable resource enabling easy and unrestricted access to such data. We hypothesized that hepatic transcriptome differed between groups, and this was also regulated by food intake. We obtained liver tissue by transjugular liver biopsies from patients with NAFLD (n = 9, mean age 49 (16 SD) y, BMI 35 (5) kg/m2), cirrhosis (n = 9, age 61 (11) y, BMI 32 (5) kg/m2) and healthy controls (n = 10, age 25 (3) y, BMI 23 (3) kg/m2). The hepatic transcriptome was sequenced using NGS and evaluated in bioinformatic analyses to assess differentially expressed genes (DEG) and gene ontology biological processes (GOBP). We identified 553 DEG between healthy controls and patients with NAFLD, 5527 DEG between healthy controls and patients with cirrhosis, and 3898 DEG in NAFLD compared with cirrhosis. A hitherto uncharacterized gene (MET proto-oncogene) was differentially expressed in human NAFLD and cirrhosis. The hepatic transcriptome changed significantly during a standardized meal and these changes were blunted in patients with NAFLD and cirrhosis. GOBP analyses revealed an increase in pro-inflammatory and pro-fibrotic genes in NAFLD and cirrhosis, as well as a decrease in genes related to metabolism. Data were made browsable using two web-based apps. The hepatic transcriptome is differentially regulated by a standardized meal in healthy individuals compared to patients with fatty liver disease.